2004
DOI: 10.1007/s10143-004-0370-5
|View full text |Cite
|
Sign up to set email alerts
|

Topical application of mitomycin C prevents epineural scar formation in rats

Abstract: The role of topically applied mitomycin C in preventing postoperative perineural fibrosis was examined by gross anatomical dissection and histological analysis in rats. The sciatic nerve was exposed bilaterally in 24 Wistar adult male rats, and an abrasion injury was produced on the exposed surface of the biceps femoris muscle in all animals. In the experimental group, cotton pads soaked with mitomycin C (0.5 mg/ml) were placed around the nerves for 5 min, whereas cotton pads soaked with saline were applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Prevention is a far more desirable goal (Gomel et al, 1996;Mettler, 2003;Scott-Coombes et al, 1993), and much effort has been expended on adhesion prevention using various chemical compounds and barriers (Corrales et al, 2008;Guo et al, 2009;Ilbay et al, 2004;Kutlay et al, 2004;Mettler et al, 2003;Oncel et al, 2004). Systematic reviews of these treatments have reported that none consistently prevent adhesion formation (Kumar et al, 2009;Metwally et al, 2006).…”
Section: Introductionmentioning
confidence: 96%
“…Prevention is a far more desirable goal (Gomel et al, 1996;Mettler, 2003;Scott-Coombes et al, 1993), and much effort has been expended on adhesion prevention using various chemical compounds and barriers (Corrales et al, 2008;Guo et al, 2009;Ilbay et al, 2004;Kutlay et al, 2004;Mettler et al, 2003;Oncel et al, 2004). Systematic reviews of these treatments have reported that none consistently prevent adhesion formation (Kumar et al, 2009;Metwally et al, 2006).…”
Section: Introductionmentioning
confidence: 96%
“…Single applications of scar‐suppressing drugs with reproducible results are well published in Refs. Some groups could even show that topical exposition of drugs to injured nerves for 5 min leads to significant differences . Thus, IL10 incorporated in polymerized fibrin with release over a time period of almost 2 weeks as used in our study is likely to be sufficient.…”
Section: Discussionmentioning
confidence: 81%
“…In the clinical course tethering of the nerves results in not only pain but also sensorial and motor deficits due to compression of the nerves (1,5,26,33). Preventing from or reduction in epineural scarring increases peripheral nerve surgery success, decreases the complications and facilitates further secondary operations (12,34).…”
Section: Resultsmentioning
confidence: 99%